Capital market dynamics and economic growth trend in Nigeria - Abdulrauf, Abolarin, Akinwale; Olajide, Oladipo, S.; Akintunde, Yusuf, Wasiu; Ebunoluwa, Oyegoke, O. (International Journal of Economics and Financial Modelling, 2025)
This study investigates the dynamics of capital market growth and its impact on economic growth in Nigeria from 1990 to 2024, focusing on the contribution of the capital market to GDP, as well as the short-term and long-term effects on economic trends. Secondary data from reputable sources were analyzed using multiple linear regression approach, to quantify the influence of various capital market indicators, including total market capitalization, gross capital formation, and trading volumes, on GDP growth. Additionally, the study explores the role of counter-cyclical factors within the capital market across different business cycles, providing insights into how these dynamics can enhance economic resilience during downturns. The Short-Run Estimates found that (SMC) and (TMC) have a significant positive impact on Real Gross Domestic Product (RGDP); while the Long-Run Analysis suggests that a stronger stock market, measured by the All Share Index (ASI), is associated with a more robust economy, indicating it is a foundational component of sustained economic growth. The study demonstrates the significant influence of Nigeria's capital market dynamics on its economic growth The findings are expected to inform policymakers and market participants about the significance of capital market activities in fostering sustainable economic growth in Nigeria.